2017
DOI: 10.1155/2017/4810123
|View full text |Cite
|
Sign up to set email alerts
|

Dental Implant in the Canalis Sinuosus: A Case Report and Review of the Literature

Abstract: The canalis sinuosus is a neurovascular canal, a branch of nerve of infraorbital canal, through which the anterior superior alveolar nerve passes and then leans medially in course between the nasal cavity and the maxillary sinus, reaching the premaxilla in the canine and incisor region. The purpose of this article is to report a case with the presence of canalis sinuosus, in order to alert and guide professionals and discuss the morphology of this anatomical variation avoiding trans- and postsurgical disorders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(73 citation statements)
references
References 14 publications
0
63
0
2
Order By: Relevance
“…There are several case reports with dental implants placed in the anterior maxilla and CS damage, presenting the same neurological symptomatology [9,17]; however, this case additionally contributes the symptoms of trigeminal neuralgia [27] as pain irradiation in the back of the head and no intraoperative excessive bleeding rather than the usual one during the implant site preparation. The tests with the different types of local nerve blocks showed a good diagnostic efficacy indicating the damaged infraorbital nerve branch.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…There are several case reports with dental implants placed in the anterior maxilla and CS damage, presenting the same neurological symptomatology [9,17]; however, this case additionally contributes the symptoms of trigeminal neuralgia [27] as pain irradiation in the back of the head and no intraoperative excessive bleeding rather than the usual one during the implant site preparation. The tests with the different types of local nerve blocks showed a good diagnostic efficacy indicating the damaged infraorbital nerve branch.…”
Section: Discussionmentioning
confidence: 79%
“…For example, Machado et al [9] presented two case reports where patients suffered from pain and it was immediately relieved after implant extractions that had been placed with CS damage. Also, McCrea [14] and Arruda et al [17] reported different cases in which dental implant placement in the anterior maxilla in the CS led to persistent pain, and the patient's symptoms were resolved with the following removal of the implant. However, Shaeffer [18] reported a case of intractable pain following implant placement in the upper left first premolar region and the pain did not subside following the extraction of the implant.…”
Section: Introductionmentioning
confidence: 99%
“…BAENA-CALDAS, G. P.; RENGIFO-MIRANDA, H. L.; HERRERA-RUBIO, A. M.; PECKHAM, X. & ZÚÑIGA, J. R It is also associated with complications by direct or indirect injury to the anterior superior alveolar neurovascular bundle, such as intraoperative bleeding, changes in the overall sensitivity of the territory of ASAN, and difficulty in osseointegration of implants (Arruda et al, 2017). For example, Shelley et al (1999) reported a case in which an abnormal extension of this canal was mistaken for a periapical lesion on an intraoral x-ray.…”
Section: Pathwaymentioning
confidence: 99%
“…Fracture of the bone overlying the CS can result in posttraumatic midface pain localized to the central incisors, lateral incisors, canines, or anterior maxilla because this region covers by a thin bone [10].…”
Section: Discussionmentioning
confidence: 99%
“…Machado et al [9] reported a clinical case who was installed dental implants in the anterior region of the maxilla and presented postoperative pain and the postoperative CBCT showed a close relationship of the implants with the accessory canal of the CS. Moreover, Arruda et al [10] reported a case with notified paresthesia and pain in the right upper lip region after the installation of a dental implant. Then CBCT was performed and revealed the presence of CS, located between the apical region of the implant and in the upper lateral incisor area and the upper canine apex.…”
Section: Discussionmentioning
confidence: 99%